Realistic Parallel Programming Productivity. - Siegel, Stephen F. (Communications of the ACM, 2015)
A letter is presented from a reader responding to the article "A Decade of Progress in Parallel Programming Productivity" by John T. Richards and others from the November 2014 issue.